IMPROVING TEACHER'S ABILITY TO MAKE LESSON PLAN BASED ON HIGH ORDER THINKING SKILLS (HOTS) THROUGH GROUP GUIDANCE - Ruwah Santosa, Edy (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the lack of teachers' ability to prepare learning that develops high-level thinking skills (HOTS) of students. Therefore, this research aims to improve the ability of teachers to prepare lesson plans based on HOTS. This study used an action research design conducted at SMPN 2 Cerenti with 21 research subjects. Data were analyzed using observation sheets to assess the ability of teachers in preparing lesson plans based on HOTS. The results of the study showed that the ability of teachers in the first cycle reached 60.2%, which was categorized as enough, and in the second cycle, it reached 78.6%, which was categorized as good. Based on the results of the study, it can be concluded that the ability of teachers at SMPN 2 Cerenti in preparing lesson plans based on HOTS has increased through group guidance.